Determinar la presencia de anemia mediante la realización de hemoglobina, hematocrito y volumen corpuscular medio en pacientes pediátricos que acuden al centro de Salud Motupe - Masache Jiménez, Andrea Beatriz (2015)
The presence of anemia in pediatric patients is a troubling condition, as the result of suffering from this disease manifests with stunted growth and impairs cognitive function. Iron deficiency anemia is the most common cause of anemia in children, especially preschoolers, there are few studies on the subject in our locality, for this reason was conducted this research, entitled: ¨DETERMINE THE PRESENCE OF ANEMIA BY PERFORMING HEMOGLOBIN, HEMATOCRIT AND mean corpuscular volume IN PEDIATRIC PATIENTS attending Centro de salud MOTUPE¨. In this study, the following results were obtained: the presence of iron deficiency anemia is determined in 16% of the 63 studied patients. The 10% correspond to the gender male; the largest number of cases is in the ages between 4-5 and 5-6 years with 2 cases respectively. In the gender female, we find to the 6%, the highest number of cases occurred in the age range of 1-2 years with 2 cases. In addition, hemoglobin of 16% of patients studied presented values below 11.5 g / dl, while 83% showed normal values. As for the results of hematocrit, 16% had values below 35% and 83% of the cases had normal values. Finally, 38% of patients had values of MCV below of 79fl, while the remaining 62% showed normal values. Keywords: anemia, iron deficiency, hemoglobin, hematocrit, mean corpuscular volume.